Matrine Promotes Human Myeloid Leukemia Cells Apoptosis Through Warburg Effect Mediated by Hexokinase 2 - Lin, Guibin; Wu, Yangzhe; Cai, Fengtao; Li, Zhen; Su, Shixin; Wang, Jian; Cao, Jialin; Ma, Lingdi (Frontiers in Pharmacology, 2019)
Matrine, an alkaloid compound isolated from the medicinal plant Sophora flavescens, inhibits many types cancer proliferation. However, the precise mechanism of the matrine anti-human chronic myeloid leukemia remains unclear. In this study, we showed that matrine significantly inhibited the cell proliferation and induced apoptosis by regulating Warburg effect through controlling Hexokinases 2 (HK2) expression in myeloid leukemia cells. Interestingly, Matrine inhibited the expression of HK2 mediated by reduction of c-Myc binding to HK2 gene intron, led to down-regulation of HK2, which up-regulated pro-apoptotic protein Bad and then induced apoptosis. We further demonstrated that matrine could synergize with lonidamine, an inhibitor of HK2, for the treatment of myeloid leukemia, both in vitro and in vivo. Taken together, our findings reveal that matrine could promote human myeloid leukemia cells apoptosis via regulating Warburg effect by controlling HK2.